Mutational spectra induced under distinct excision repair conditions by the 3 methylating agents N-methyl-N-nitrosourea, N-methyl-N'-nitro-N-nitrosoguanidine and N-nitrosodimethylamine in postmeiotic male germ cells of Drosophila. - Nivard, M.J.M.; Pastink, A.; Vogel, E.W. (Mutation Research, 1996)
This paper describes the analysis of mutations induced at the vermilion locus in postmeiotic male germ cell stages of Drosophila exposed to 3 different N-methyl-N-nitroso compounds: N-methyl-N-nitrosourea (MNU); N-methyl-N'-nitro-N-nitrosoguanidine (MNNG); and N-nitrosodimethylamine (DMN). With MNU and DMN, the impact of DNA nucleotide excision repair (NER) on the spectra of mutations was studied. Mutants were isolated from F1 (mutations fixed before the first mitotic replication after fertilization) and F2 (mutations fixed following one or more mitotic replications; mosaics in F1) generations. The vermilion system enables the analysis of both intra- and inter-locus DNA changes for which several techniques have been adapted: (1) amplification of the vermilion gene by PCR, cloning of the fragment and sequence analysis of ssDNA; (2) Southern blot hybridization; and (3) cytological analysis of polytene chromosomes. In total, 49 MNU (26 from the exr+ genotype and 23 from the exr- genotype), 47 DMN (28 from the exr+ genotype and 19 from the exr- genotype) and 16 MNNG-induced mutations were characterized. The F1 spectra of all 3 agents contained base-pair changes and deletions (intra- and multi-locus) in a ratio of roughly 1 to 1, indicating a significant contribution of nitrogen DNA adducts to the spectra. In all F2 spectra the levels of base-pair changes were significantly higher compared to those in the F1 spectra, a finding also made for methyl methanesulfonate-induced mutations in earlier studies. There is an increase of mutations of, especially, the transversion types of mutations under exr- conditions in comparison to the exr+ situation. The induced transversions, clearly present in all spectra (exr+ and exr-), are presumably caused by N-methyl DNA adducts, which upon release from the DNA backbone lead to apurinic sites in a time-related process. Regarding the occurrence of transitions, it turned out for all 3 mutagens that the AT-->GC type strongly dominated the GC-->AT transitions. This suggest that O6-methylguanine is efficiently repaired, in contrast to O4-methylthymine. Based on the data obtained in the vermilion system with ENU, we propose, in addition, that the Drosophila alkyltransferase system repairs O6-methylguanine more efficiently than O6-ethylguanine.